Hornwort Stomata: Architecture and Fate Shared with 400-Million-Year-Old Fossil Plants without Leaves. Issue 2 (18th April 2017) - Renzaglia, Karen S.; Villarreal, Juan Carlos; Piatkowski, Bryan T.; Lucas, Jessica R.; Merced, Amelia
Abstract : Guard cells in hornwort develop wall thickenings, open, die, and collapse, similar to the oldest fossil plants, and in synchrony with sporogenesis, drying of internal fluids, and sporophyte maturation. Abstract: As one of the earliest plant groups to evolve stomata, hornworts are key to understanding the origin and function of stomata. Hornwort stomata are large and scattered on sporangia that grow from their bases and release spores at their tips. We present data from development and immunocytochemistry that identify a role for hornwort stomata that is correlated with sporangial and spore maturation. We measured guard cells across the genera with stomata to assess developmental changes in size and to analyze any correlation with genome size. Stomata form at the base of the sporophyte in the green region, where they develop differential wall thickenings, form a pore, and die. Guard cells collapse inwardly, increase in surface area, and remain perched over a substomatal cavity and network of intercellular spaces that is initially fluid filled. Following pore formation, the sporophyte dries from the outside inwardly and continues to do so after guard cells die and collapse. Spore tetrads develop in spore mother cell walls within a mucilaginous matrix, both of which progressively dry before sporophyte dehiscence. A lack of correlation between guard cell size and DNA content, lack of arabinans in cell walls, and perpetually open pores are consistent with the inactivity of hornwort stomata. Stomata are expendable in hornworts, as they have been lost twice in derived taxa. Guard cells and epidermal cells of hornworts show striking similarities with the earliest plant fossils. Our findings identify an architecture and fate of stomata in hornworts that is ancient and common to plants without sporophytic leaves.